2007
DOI: 10.1186/1472-6963-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Use frequency of traditional Chinese medicine in Taiwan

Abstract: Background: Use of Traditional Chinese medicine (TCM), an important category of complementary and alternative medicine (CAM), has increased substantially in Western countries during the past decade. Use of TCM is also widespread in the Chinese population. However, few informative data have been obtained to date by large-scale investigations of TCM use in the Chinese population. This study was aimed at elucidating the demographics and patterns of TCM use in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
226
9
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(253 citation statements)
references
References 48 publications
17
226
9
1
Order By: Relevance
“…A previous study showed that most CM services were provided by clinics (82.6%) rather than hospitals. 34 However, our study found that 32.4% of CM visits of prostate cancer patients were provided by private clinics and 67.6% by hospitals, mostly by WM hospitals with CM sections rather than hospitals of CM. This reflects that CM users with prostate cancer may prefer to be treated at the same hospital where they received WM.…”
Section: Discussionmentioning
confidence: 54%
“…A previous study showed that most CM services were provided by clinics (82.6%) rather than hospitals. 34 However, our study found that 32.4% of CM visits of prostate cancer patients were provided by private clinics and 67.6% by hospitals, mostly by WM hospitals with CM sections rather than hospitals of CM. This reflects that CM users with prostate cancer may prefer to be treated at the same hospital where they received WM.…”
Section: Discussionmentioning
confidence: 54%
“…Currently, using of oriental medicine/CAM and popularity of them have been increasing worldwide among general population (Chen et al, 2007;Braun et al, 2013). Along with this, it has recently been widely spread the introduction of oriental medicine/CAM courses in an undergraduate medical education curriculum (Wetzel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Au plan quantitatif,l er ecours à l'acupuncture ne représenterait, en pays asiatique, que 10 à 15 %d e l'ensemble des traitements de MTC [1], alors que les traitements par herbes médicinales constituent plus de 85 %d es recours à la MTC.…”
Section: Introduction Et Historique De L'ebm En Acupunctureunclassified